2016
DOI: 10.1021/acsami.6b13164
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ensemble Plasmon Line Widths and Enhanced Two-Photon Luminescence in Anodically Formed High Surface Area Au–TiO2 3D Nanocomposites

Abstract: Localized surface plasmon resonances (LSPR) in TiO nanorod and nanotube arrays decorated by gold nanoparticles can be exploited to improve photocatalytic activity, enhance nonlinear optical coefficients, and increase light harvesting in solar cells. However, the LSPR typically has a low quality factor, and the resonance is often obscured by the Urbach tail of the TiO band gap absorption. Attempts to increase the LSPR extinction intensity by increasing the density of gold nanoparticles on the surface of the TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…High‐resolution X‐ray photoelectron spectroscopy (XPS) showed that the Au 4f of the Au/TiO 2 sample shifted to a lower binding energy after the annealing treatment (Figure b), suggesting the occurrence of fine interfacial contact and electron transfer from TiO 2 to Au NPs. The high‐resolution transmission electron microscopy (HRTEM) image revealed that intimate physical contact was formed at the Au NPs/TiO 2 interface (Supporting Information, Figure S3), which is important for hot electron injection from Au to TiO 2 upon SPR excitation . Figure c shows the absorption spectra of the pure TiO 2 and AuNPs/TiO 2 photocatalysts.…”
Section: Figurementioning
confidence: 99%
“…High‐resolution X‐ray photoelectron spectroscopy (XPS) showed that the Au 4f of the Au/TiO 2 sample shifted to a lower binding energy after the annealing treatment (Figure b), suggesting the occurrence of fine interfacial contact and electron transfer from TiO 2 to Au NPs. The high‐resolution transmission electron microscopy (HRTEM) image revealed that intimate physical contact was formed at the Au NPs/TiO 2 interface (Supporting Information, Figure S3), which is important for hot electron injection from Au to TiO 2 upon SPR excitation . Figure c shows the absorption spectra of the pure TiO 2 and AuNPs/TiO 2 photocatalysts.…”
Section: Figurementioning
confidence: 99%
“…Two-photon luminescence (TPL) is a photoluminescence technique utilized to analyze the plasmonic response of noble metal nanoparticle systems [ 195 , 196 , 197 ] in which the noble metal nanoparticle is excited by the simultaneous absorption of two photons, usually in the infrared regime, with sufficiently intense laser illumination [ 198 ]. Single ultraviolet photon excited photoluminescence in plasmonic nanostructures exhibits a linear dependence of the emission intensity on the excitation power, and is understood to proceed through the recombination of d -band holes with sp -band electrons, as previously mentioned.…”
Section: Probing Hot Electronsmentioning
confidence: 99%
“…In principle, steady-state and time-resolved TPL could also be used to probe the dynamics of carriers created by interband transitions, specifically to understand whether photoexcited electrons in the several micrometer-thick noble metal–semiconductor nanocomposites are transferred to the semiconductor or not (i.e., by observing if some or all of the two-photon photoluminescence of the isolated noble metal nanoparticle is quenched in the presence of the semiconductor), and to measure the time-scales of competing processes, such as plasmon-mediated radiative recombination; however, very few reports have actively used TPL to examine phenomena specifically related to hot electrons. TPL was used by Farsinezhad et al [ 195 ] in demonstrating the effectiveness of a novel plasmonic nanoparticle-embedded nanotube structure in generating a high local field enhancement that outperformed a plasmonic nanoparticle-decorated anodic nanotube structure. ( Figure 17 ) Localized surface plasmon resonances, and surface plasmon modes are both influenced by the local dielectric properties, and fluctuations in the charge density of the given plasmonic material.…”
Section: Probing Hot Electronsmentioning
confidence: 99%
See 2 more Smart Citations